Upaya Penegakan Hukum Balap Liar Di Kota Surakarta Jawa Tengah: (Studi Kasus : Satlantas Polresta Surakarta) - Prabowo, Ilham Hendra; Santoso, Aris Prio Agus (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Illegal motorbike and car racing behavior in the city of Surakarta has disturbed the public. Illegal racing behavior has been categorized as a social pathological condition so that it needs to be dealt with immediately to prevent more victims from falling. Illegal racing is carried out by teenagers without paying attention to traffic regulations, not using established motorbike safety standards (not wearing helmets, jackets and leg protectors, full exhaust, no mirrors, no number plates). Illegal racing seriously endangers the safety of the perpetrators and surrounding road users. Illegal racing is usually done at night. The aim of this research is to find out the general picture of illegal racing in real terms and to find out how criminal law is enforced against perpetrators of illegal motorbike or car racing at the Surakarta Police Traffic Unit. This research method uses normative legal research methods using qualitative data analysis. The results of the research show that the majority of illegal racing activities in the city of Surakarta are carried out by teenagers who want to show their identity and share their hobby of driving but do not pay attention to traffic regulations, resulting in irregularities and unlawful acts as well as a lack of knowledge among teenagers about traffic regulations. Enforcement of criminal law against illegal racing activities is carried out with preventive and repressive measures. Factors that influence the effectiveness of law enforcement are legal factors, law enforcement factors, facility factors, community factors and cultural factors. It is hoped that the existence of law enforcement and outreach to juvenile perpetrators of illegal racing can minimize the existence of illegal racing activities in the city of Surakarta.